The Effect of Compound Skill Exercises on Developing Shooting Accuracy Among Futsal Players of The Al-Rusafa Third Education Team (Journal of the College of Basic Education, 2026)
The aim of this study was to identify the effect of compound skill exercises on improving shooting accuracy among players of the Al-Rusafa Third Education football team. The researcher used the experimental method with a one-group design (pre-test and post-test) due to its suitability to the nature of the research problem. The research sample was intentionally selected and consisted of (12) players out of (18), representing (67%) of the research population. A shooting accuracy test was used as a tool to measure performance level. The pre-test was conducted before implementing the training program. Then, compound skill exercises were applied, including real-game situations that combined passing, ball control, movement, and shooting, over a specified period of time. After completing the program, the post-test was conducted Appropriate statistical methods were used, including the arithmetic mean, standard deviation, and the paired sample t-test to analyze the data. The results showed statistically significant differences between the pre-test and post-test in favor of the post-test, indicating the effectiveness of compound skill exercises in improving shooting accuracy. The researcher recommends adopting compound skill exercises within training sessions due to their positive effect on developing players’ technical performance, especially shooting skill.